Implementation of Individual Learning Methods in Reading Lessons at Tadika Tahfidz Nur Furqan Malaysia - Chairunnisa, Maghfirah; Rahimah, Rahimah (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Acquiring education is crucial for attaining success in life, and top-notch education is the cornerstone for producing competent workforce. Malaysia, being one of the nations with the finest education system, places significant emphasis on early childhood education by implementing the National Preschool Standard Curriculum (KSPK). Tadika Tahfidz Nur Furqan implements individual learning methods to enhance the reading skills of children aged between 4-6 years. The ability to read is a crucial aspect of preschool education, and this study aims to examine the effectiveness of these individual learning methods in reading lessons at Tadika Tahfidz Nur Furqan. The study found that this teaching method has multiple advantages such as adapting to individual student abilities, quick progress, parental involvement, material adaptation, and the use of individual record books. However, it also has some drawbacks such as limited parental involvement, difficulty in handling student diversity, and time constraints. It is crucial for the school to focus on students with special needs and encourage parental involvement to provide a more well-rounded education. This study examines individual learning methods in early childhood education in Malaysia.